Demand Determinants of Cruise Tourism in Competitive Markets: Motivation, Preference, and Intention - Jamie Chen (European Regional Science Association (ERSA), 2015)
The purpose of this study is to develop and estimate an integrated structural path model of the determinants of cruise demand, based on the nexus of motivation, preference, and intention of cruise tourists. The paper aims to identify the drivers of this demand in a growing competitive world market. Our model results show that different cruise motives have significant positive or negative effect on specific customer preferences and intentions, while some significant relationships between specific cruise preferences and intentions are also found. Based on our structural path model, a T-test is applied to compare the differences of cruise motivations and cruise preferences between the growing Asian market and the global cruise market, in order to trace the instrumental determinants of cruise passengers, leading to a new understanding of cruise competitiveness in different regional markets.
Keywords: 330; structural equation modelling; cruise; competitiveness; motivation; preference; intention